1989
DOI: 10.3171/jns.1989.71.1.0049
|View full text |Cite
|
Sign up to set email alerts
|

Unenhanced and gadolinium-DTPA-enhanced MR imaging in postoperative evaluation in pediatric brain tumors

Abstract: Gadolinium-diethylenetriaminepenta-acetic acid (Gd-DTPA) is a chelated paramagnetic contrast agent under clinical trial for use in magnetic resonance (MR) imaging. The increased signal intensity following the intravenous infusion of contrast medium may improve the ability of MR imaging to delineate tumors. The use of this method in 15 pediatric patients with suspected brain-tumor recurrence was analyzed. All 15 patients underwent postoperative Gd-DTPA-enhanced MR imaging, and residual tumor was demonstrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…2 Because tumor response to adjuvant therapy is also assessed by CT and MR imaging, these modalities have become integral to the postoperative standard of care management of neurooncological disease. 5,10,13,34,35…”
Section: Magnetic Resonance Imaging Versus the Surgeon's Estimation Tmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Because tumor response to adjuvant therapy is also assessed by CT and MR imaging, these modalities have become integral to the postoperative standard of care management of neurooncological disease. 5,10,13,34,35…”
Section: Magnetic Resonance Imaging Versus the Surgeon's Estimation Tmentioning
confidence: 99%
“…For these reasons MR imaging has become the imaging study of choice for postoperative assessment and surveillance of patients with brain tumors. 13,33…”
Section: Magnetic Resonance Imaging Versus Computerized Tomography Tomentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, while many studies have confirmed the "added value" of contrast-enhanced images for pediatric MRI (97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108), the question is whether or not routine contrast administration in children is warranted. Given that there appears to be an identical safety profile in the pediatric and adult populations, it seems reasonable to administer Gd-based agents to children in the same basic situations considered for adults, particularly in the evaluation of neoplastic or inflammatory disease.…”
Section: Pediatricsmentioning
confidence: 99%